2009
DOI: 10.1039/b907316g
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-phase broadband cavity enhanced absorption spectroscopy (BBCEAS) studies in a 20 cm cell

Abstract: Sensitive liquid-phase measurements have been made in a 20 cm cell using broadband cavity enhanced absorption spectroscopy (BBCEAS). The cavity was formed by two high reflectivity mirrors which were in direct contact with the liquid-phase analytes. Careful choice of solvent was required to minimise the effect of background solvent absorptions. Measurements were made on the broad absorber Sudan black, dissolved in acetonitrile, using a white LED light source and R $ 0.99 cavity mirrors, leading to a cavity enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…There are clear advantages in having this capability: to measure several compounds simultaneously and to increase the amount of information in a particular measurement, thereby statistically enhancing the output (for example, in measuring several spectral lines to record an isotopic ratio); and to improve specificity, where target species exhibit relatively broad spectral signatures. Several schemes have been reported for BB-CEAS involving different sources and detection apparatus, and including application to the measurement of liquid and/or surface borne species [10,13,14,15,18,19]. On the whole, these studies have been at visible wavelengths, and as broad band optical sources both light emitting diodes and discharge lamps have featured predominantly and have been used with either imaging spectrometers or Fourier transform interferometers as detection systems.…”
Section: Introductionmentioning
confidence: 99%
“…There are clear advantages in having this capability: to measure several compounds simultaneously and to increase the amount of information in a particular measurement, thereby statistically enhancing the output (for example, in measuring several spectral lines to record an isotopic ratio); and to improve specificity, where target species exhibit relatively broad spectral signatures. Several schemes have been reported for BB-CEAS involving different sources and detection apparatus, and including application to the measurement of liquid and/or surface borne species [10,13,14,15,18,19]. On the whole, these studies have been at visible wavelengths, and as broad band optical sources both light emitting diodes and discharge lamps have featured predominantly and have been used with either imaging spectrometers or Fourier transform interferometers as detection systems.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported that combine different broad-band sources such as arc-lamps [1][2][3][4][5][6] and light emitting diodes (LEDs) [7][8][9][10][11][12] with dispersive and interferometric detection schemes to detect gas phase species such as iodine oxides, 5 NO x compounds, 7,8,10,11 and solutions containing dyes (e.g. coumarin 334, brilliant blue-R, and rhodamine B and 6G) 9,12,13 which absorb at visible wavelengths. High power supercontinuum sources have also been demonstrated in cavity enhanced spectroscopy, 14,15 but these are devices that represent a major financial investment, generate a wide spectral output, usually much larger than the stop band of the high reflectivity cavity mirrors, and generally have optimised performance in the visible and near-IR (<1 mm).…”
Section: Introductionmentioning
confidence: 99%
“…This nonlinear behavior is most obvious under experimental conditions in which the optical absorption loss dominates the total per-pass losses. The nonlinear behavior is shown in Figure 4 from Seetohul et al [21]. This adds additional difficulty to quantitative analysis using CES.…”
Section: Liquid Phase Ces Experiments Within Linear Resonatorsmentioning
confidence: 99%
“…This results in distortion of absorption spectra compared to the case of a uniform path length. Figure 3 shown below from Seetohul et al [21] illustrates cavity enhancement factor can vary 2 Journal of Spectroscopy 3-fold as a function of wavelength. The absorption spectrum collected by the CES spectrometer is consequently distorted as illustrated in Figure 3(b).…”
Section: Liquid Phase Ces Experiments Within Linear Resonatorsmentioning
confidence: 99%
See 1 more Smart Citation